2018
DOI: 10.1002/mabi.201800220
|View full text |Cite
|
Sign up to set email alerts
|

Role of Skin Layers on Mechanical Properties and Supercontraction of Spider Dragline Silk Fiber

Abstract: Spider dragline silk is a composite biopolymer that harbors extraordinary mechanical characteristics, and consists of a hierarchically arranged protein core surrounded by outer "skin" layers. However, the contribution of the successive fiber layers on material properties has not been well defined. Here, the influence of the different components on the physicochemical and mechanical properties of dragline is investigated. The crystal structure and the mechanical properties are not changed significantly after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Meanwhile, the dragline silks showed relatively rough fracture surface when the strain rates more than 3.3 × 10 −2 s −1 were applied. The dragline silk consists of a hierarchically arranged protein core surrounded by outer skin layers 25 . The protein core is composed of fibrils that are formed by compact assembly of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the dragline silks showed relatively rough fracture surface when the strain rates more than 3.3 × 10 −2 s −1 were applied. The dragline silk consists of a hierarchically arranged protein core surrounded by outer skin layers 25 . The protein core is composed of fibrils that are formed by compact assembly of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that the remarkable mechanical performance of spider silk dragline originates from a hierarchical organization of proteins into a hydrogen bonded structure of ordered crystalline β-sheets, embedded in a disordered amorphous matrix [ 1 , 2 , 3 , 4 , 5 , 6 ]. However, at the mesoscale, it has also been shown that silk assembles into nanofibrils with diameters ranging from ~30 nm [ 3 ] to more than 100 nm [ 2 , 5 ] and that a fibre has structurally and functionally distinct regions; a load bearing core (consisting of inner (1800–2300 nm), and outer (300–400 nm) sections [ 2 , 7 , 8 ]) surrounded by protective lipid (10–20 nm), glycol (40–100 nm), and skin (50–100 nm) layers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there have been several concerted modelling efforts to relate silk’s structures to its mechanical properties [ 3 , 4 , 5 , 6 , 7 , 8 , 18 , 19 ], accounting for the precise contributions of each of these structural elements on a fibre’s mechanical response has been inconclusive. Consider, e.g., the role played by the interfaces between the fibrils, which some studies define as mechanically weak and responsible for easy slippage of adjacent fibrils [ 6 ], while other studies observe the presence of heterogeneous protrusions along such surfaces determining a non-slip kinematics and energy dissipation due to interlocking effects [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a typical dragline fiber of 5 µm diameter, the coating is approximately 100 nm in thickness and can be further differentiated into a waxy lipids and a glycoprotein layer, which together are attributed with the control of moisture content, antimicrobial properties, and pheromonal communication (Augsten et al, 2000;Sponner et al, 2005Sponner et al, , 2007. Although it is chemically diverse, the contribution of the coating to the fiber's overall tensile behavior has been proposed to be very small (Yazawa et al, 2018). The underlying skin is of similar thickness to the coating and has been found to compose mostly of minor ampullate spidroin protein (MiSp) which is the main component of minor ampullate fibers (Sponner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%